An innovative paradigm of intensive care: hot pot pattern - Zhang, Kai; Zhou, Yiping; Cao, Lanxin; Fan, Yushi; Cui, Wei; Zhang, Gensheng (Frontiers in Medicine, 2025)
This paper proposes the novel “Hot Pot Pattern” to conceptualize intensive care. The conventional treatment and monitoring methods form the foundational “Hot Pot Base,” and individualized interventions form the “Hot Pot Ingredients.” This model elucidates the integration of standardized care with personalized medicine inherent in intensive care management.